Pengembangan Materi Pembelajaran Gramatika Bahasa Arab (Nahwu) di Pesantren Bayt Tamyiz Indramayu - Syathybie, Aca; Sauri, Sofyan (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
The problem in this research is the study of arabic grammar learning method (Nahwu) at Bayt Tamyiz Islamic Boarding School Indramayu. The study is focused on objective program, evaluation and obstacles in learning arabic grammar (Nahwu). This research is qualitative research with grounded research (field work) approach. The source of data is the leader and teachers at Bayt Tamyiz Islamic Boarding School Indrawayu West Java. In this study found findings of them, Tamyiz book discussion begins with al-sentences (words) letters, noun and verb, traits that noun beginning ma mi mu, classify kana and laisa as letters, characteristic verb present countinous tense 'passive prefix (yu, tu, u, nu),the mujarrad is tsulâtsi verb and tsulâtsî noun, the maqshûr that ends with " alif" as al-dunya, al-mushtafâ and Mûsâ then mabnî, the manqûsh' is mabni for rafa 'and jarr, but when nashab, then' fathah be mu'rab. Noun number called number ibtidaiyah. In fact the word that divides the number of primary into noun and verb. The result of this research indicate corrections to the findings and innovations in the book of Tamyiz, is that the huruf can not be sorted in the first place because it always needs to isim and fi’il. Characteristic of isim it not begining ma mi mu, because confuse students at said noun mazzaqa, mîkho and musiha. Kana and laisa are not letters but they were fi’il, because they received all signs of fi’il. Ismiyah sentence called ibtidaiyah sentence, because word of ibtidaiyah that divide the s3entence into Ismiyah and fi’liyyah. The conclution of this research that the aplication of Arabic grammar learning method (Nahwu) at Bayt Tamyiz Islamic Boarding School is quite effective. And there are some success and obstacles factors in the grammar lesson for students, without disrupting the routine proccess of teaching and learning activities. Keywords: arabic learning, grammar, learning method